ANALYSIS OF PATIENT SATISFACTION WITH THE QUALITY OF OUTPATIENT SERVICES - Sianturi, Ladonna; Ali Harokan; Arie Wahyudi (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Satisfaction is an individual's emotional state of pleasure or dissatisfaction by comparing perceived service performance according to expectations. Factors that influence hospital satisfaction are tangible, reliability, responsiveness, assurance and empathy. This study aims to determine factors related to outpatient patient satisfaction at the Rupit Regional General Hospital, North Musi Rawas Regency in 2024. The design of this research is quantitative with a cross-sectional approach. The sample in this study amounted to 93 people. The sampling method uses purposive sampling. Inclusion criteria were outpatients and those willing to be respondents. This research was carried out on March 4-31 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the research show that there is a relationship between reliability (p value 0.001) and responsiveness (p value 0.009) with outpatient satisfaction at Rupit Hospital, North Musi Rawas Regency in 2024. The most dominant factor in outpatient satisfaction at Rupit Hospital, North Musi Rawas Regency in 2024. 2024, namely reliability (p value 0.001), (OR 0.21). The conclusion is that there is a relationship between reliability and responsiveness and outpatient satisfaction at the Rupit Hospital, North Musi Rawas Regency in 2024. The hospital should provide services quickly and provide easy service for patients.